Sosialisasi Olahraga Pickleball pada MGMP KKG PJOK di Kabupaten Tuban - SAPTO WIBOWO (DEPARTEMEN KESEHATAN DAN REKREASI UNIVERSITAS NEGERI PADANG, 2024)
The game sport that is developing, namely Pickleball, in addition to recreational and achievement sports, can be applied by Physical Education, Sports, and Health (PJOK) teachers as teaching materials on small ball games during continuous learning activities because pickleball is very easy to play for anyone. As a PJOK teacher, they are expected to be able to present interesting, creative and innovative learning goals. The purpose of this community service is to increase the insight, knowledge, and skills of PJOK teachers. The results to be achieved in this activity are 4 things, namely: (1) the PJOK teacher community network in Tuban district is integrated with Unesa, (2) the increase in knowledge related to a new sport, namely Pickleball, (3) recommendations for physical activity to improve students' physical fitness through Pickleball sports, and (4) future prospects can become a granary of potential achievements through extracurricular pathways in schools. The practical implications include the increase in PJOK teachers' understanding of game sports and the growing development of the game of Pickleball through schools. In addition, the results of this socialization can be a reference for PJOK teachers with the Pickleball game can be used as a learning video medium, new innovations in small ball learning, and as a place to find potential and talented seeds. In addition, it is a reference for the government and related parties in designing policies and programs for the development of the educational curriculum, especially in the MGMP/KKG PJOK in Tuban district.